Contrastive Study of Deep Learning in Senior and Vocational High School English Instruction - Kusuma Adilla; Semi Sukarni; Juita Triana (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
This study aims to analyze differences in the implementation of deep learning in English language instruction at Senior High Schools (SMA) and Vocational High Schools (SMK). This study employs a qualitative descriptive method, utilizing data collection techniques such as observation and interviews with two English teachers at SMA and two English teachers at SMK. The data were analyzed using an interactive analysis model that includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of deep learning in both educational levels equally apply the principles of meaningful, joyful, and mindful learning. In high schools, learning focuses more on developing critical thinking and communication skills through activities such as speaking classes and group discussions linked to students’ daily lives. Meanwhile, in vocational high schools, learning is more oriented toward workplace needs, such as job interview simulations, writing job applications, and skill-based projects aligned with students’ fields of expertise. The main difference lies in the orientation of learning, where high schools emphasize academic and communication aspects, while vocational high schools place greater emphasis on work readiness and vocational contexts. Nevertheless, both levels share the same goal: to create active, meaningful, and relevant learning experiences for students.